2012
DOI: 10.1172/jci60433
|View full text |Cite
|
Sign up to set email alerts
|

Brown adipose tissue oxidative metabolism contributes to energy expenditure during acute cold exposure in humans

Abstract: Brown adipose tissue (BAT) is vital for proper thermogenesis during cold exposure in rodents, but until recently its presence in adult humans and its contribution to human metabolism were thought to be minimal or insignificant. Recent studies using PET with 18 F-fluorodeoxyglucose ( 18 FDG) have shown the presence of BAT in adult humans. However, whether BAT contributes to cold-induced nonshivering thermogenesis in humans has not been proven. Using PET with 11 C-acetate, 18 FDG, and 18 F-fluoro-thiaheptadecano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

59
909
12
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 873 publications
(987 citation statements)
references
References 37 publications
59
909
12
7
Order By: Relevance
“…Because glucose is not the primary substrate, BAT activity based on [ 18 F]FDG uptake may underestimate and potentially miss components of BAT energy metabolism under certain physiological conditions. While [ 18 F]FDG-PET-based assessments of human BAT activity in response to acute [20,21,38,42] and chronic [2,4] cold exposure have reflected the expected outcomes based on rodent experiments, this study indicates that there are species differences for other adaptive stimuli. Although we have shown that pioglitazone reduced coldstimulated BAT glucose uptake, we cannot definitively claim that fat oxidative capacity also decreased.…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 58%
See 1 more Smart Citation
“…Because glucose is not the primary substrate, BAT activity based on [ 18 F]FDG uptake may underestimate and potentially miss components of BAT energy metabolism under certain physiological conditions. While [ 18 F]FDG-PET-based assessments of human BAT activity in response to acute [20,21,38,42] and chronic [2,4] cold exposure have reflected the expected outcomes based on rodent experiments, this study indicates that there are species differences for other adaptive stimuli. Although we have shown that pioglitazone reduced coldstimulated BAT glucose uptake, we cannot definitively claim that fat oxidative capacity also decreased.…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 58%
“…Although we have shown that pioglitazone reduced coldstimulated BAT glucose uptake, we cannot definitively claim that fat oxidative capacity also decreased. Nevertheless, previous acute cold interventions in similar participants resulted in parallel kinetics between fatty acid and glucose PET tracers [42], thus it is likely that our findings are relevant for BAT thermogenic activity. Our study design minimised the impact of individual and non-BAT [ 18 F]FDG uptake variability by conducting pre-and post-imaging on all participants, tightly controlling laboratory conditions and maximising statistical and experimental rigor by including a placebo-treated group.…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 84%
“…BAT oxidative metabolism has been shown to be a significant contributor to whole body energy expenditure. 9,10 The relatively recent "re-discovery" of BAT in adult humans and its known role in adaptive thermogenesis has made activation of this tissue a prominent focus of metabolic research. The amount of BAT in humans has been shown to vary with age, BMI, and gender, compounding the complexity of these studies.…”
Section: Adipose Tissuementioning
confidence: 99%
“…PET is a highly sensitive and specific imaging tool for studies of BAT physiology (Table 1). (Orava et al 2011, Muzik et al 2012 [ (Virtanen et al 2009, Orava et al 2011 Free fatty acid metabolism (Ouellet et al 2012) [ 18 F]FTHA 109…”
Section: Tracers For Bat Metabolic Imaging and Principles Of Modelingmentioning
confidence: 99%
“…The images were corrected for the T2*--decay effect by fitting T2*--decay parameters for fat and water signals respectively using a model similar to that described by O'Regan et al (2008).…”
Section: Phase Sensitive Reconstructionmentioning
confidence: 99%